Seed germination and seedling survival and growth in swamps dominated by palms Raphia taedigera (Arecaceae) in Tortuguero plains, Costa Rica. - Myers, Ronald L. (2013)
In the marshes dominated by palms, seeds face anaerobic substrates and long flooding periods. Some tree species are capable of growing both in flooded swamps and in areas with lower influence of the flood. I studied the potential settlement of various tree species in different macrohabitats in the Tortuguero floodplain using three experiments: (1) Manicaria saccifera and Raphia taedigera seed germination in palm-swamps and forests of slopes; (2) germination of R. taedigera seeds along a microtopographic gradient; and (3) seed germination and seedling height growth of six woody species (Dipteryx oleifera, Pterocarpus officinalis, Prioria copaifera, Pentaclethra macroloba, Carapa guianensis and Crudia acuminata) and two palms (R. taedigera and Manicaria saccifera) under different forest and swamp habitats. In the first experiment, I found that the palms germinated much earlier in the slope forest than in the palm-swamp. In the second experiment, in drier plots (less effect of flooding) germination began earlier than in the more humid plots. In the third experiment, woody species germinated faster than the studied palms, and some species do not tolerate flooded areas (marshes and swamps), so they cannot germinate or survive in them. Other woody species were removed from the slope forest, probably due to seed predators. Based on the presence or absence of these species in the environment of study were divided into: (1) obliged swamp species (R. taedigera and M. saccifera), (2) swamp intolerant (D. oleifera), and (3) facultative wetland species (P. officinalis, P. copaifera, P. macroloba, C. guianensis). Crudia acuminata does not seem to follow any of these categories.